Bio-oil production from pyrolysis of Polypropylene using dolomite catalyst - Yorinda Buyang; Yenni Pintauli Pasaribu; Paulus Mangera; Dina Kartika Maharani; Novike Bela Sumanik (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Polypropylene is converted into bio-oil through catalytic pyrolysis using dolomite as a catalyst. The purpose of this study was to determine the effect of using dolomite directly without prior treatment on the bio-oil produced from the pyrolysis of propylene plastic. The amount of loading catalyst used is 5%. Increasing the pyrolysis temperature from 350 to 450 ℃ increased bio-oil from 35.56 wt% to 64.84 wt% by reducing gas to 21.08 wt%. In thermal pyrolysis, the production of bio-oil is 85 wt% with 19.30 wt% char. In the GC-MS analysis of bio-oil from thermal and catalystic pyrolysis, the most dominant alcohol composition was obtained. Based on the result of the analysis, it can be concluded that the bio-oil obtained can be further developed into fuel.